Orai1 and Orai3 Mediate Store-Operated Calcium Entry Contributing to Neuronal Excitability in Dorsal Root Ganglion Neurons - Wei, Dongyu; Mei, Yixiao; Xia, Jingsheng; Hu, Huijuan (Frontiers in Cellular Neuroscience, 2017)
Store-operated calcium channels (SOCs) are highly calcium-selective channels that mediate calcium entry in various cell types. We have previously reported that intraplantar injection of YM-58483 (a SOC inhibitor) attenuates chronic pain. A previous study has reported that the function of SOCs in dorsal root ganglia (DRG) is enhanced after nerve injury, suggesting that SOCs may play a peripheral role in chronic pain. However, the expression, functional distribution and significance of the SOC family in DRG neurons remain elusive and the key components that mediate SOC entry (SOCE) are still controversial. Here, we demonstrated that the SOC family (STIM1, STIM2, Orai1, Orai2 and Orai3) was expressed in DRGs and STIM1 was mainly present in small- and medium-sized DRG neurons. Using confocal live cell imaging, Ca2+ imaging and electrophysiology techniques, we demonstrated that depletion of the endoplasmic reticulum (ER) Ca2+ stores induced STIM1 and STIM2 translocation, and that inhibition of STIM1 or blockage of Orai channels with pharmacological tools attenuated SOCE and SOC currents. Using the small inhibitory RNA knockdown approach, we identified STIM1, STIM2, Orai1 and Orai3 as the key components of SOCs mediating SOCE in DRG neurons. Importantly, activation of SOCs by thapsigargin (TG) induced plasma membrane depolarization and increased neuronal excitability, which were completely abolished by inhibition of SOCs or double knockdown of Orai1 and Orai3. Our findings suggest that SOCs exert an excitatory action in DRG neurons and provide a potential peripheral mechanism for modulation of pain hypersensitivity by SOC inhibition.